Basic and clinical study of efficacy and adverse effects of flumatinib in Ph+ ALL - Jun Wang; Jun Wang; Jiafei Wu; Yijing Wang; Boyue Zheng; Yu Wang; Chuanyan Jiang; Mengying Zou; Hui Li (Frontiers Media S.A., 2023)
Objective: To investigate the efficacy and safety of chemotherapy in treating Ph+ ALL based on flumatinib.Methods: The clinical data of 29 patients with Ph+ ALL receiving flumatinib-based chemotherapy in Sichuan Provincial People's Hospital from January 2020 to January 2023 were collected for analysis, with the concentrations of TKI in the peripheral blood, bone marrow, and cerebrospinal fluid of some patients monitored, Cytological experiments on SUP-B15 were conducted in a Ph+ ALL cell line.Results: A total of 29 patients were enrolled, showing the induced CR, 3-month CR, and 6-month CR rates of 96.3%, 87.5%, and 86.7%, respectively after flumatinib-based chemotherapy. The negative conversion ratio of MRD was 82.6%, 91.3%, and 95.6% in 1, 2, and 3 months after treatment, respectively, with 4.3% of patients failing the conversion in 3 months after treatment. The rates of MMR were 73.9%, 87.5%, and 93.3% in 1, 3, and 6 months after treatment, and CMR of 52.2%, 62.5%, and 73.3%, respectively. Among the 29 patients, 11 (37.9%) received transplant and the continuous flumatinib for 1 year after transplantation. The deep remission was maintained in all patients up to the time of follow-up, with the median follow-up of 12 months (1-33 months), progression-free survival (PFS) of 11 months (1-33 months), and median overall survival (OS) of 12 months (1-33 months). The adverse reactions mainly referred to myelosuppression, liver insufficiency and infection that were generally tolerable. In terms of blood concentration, the concentration of flumatinib was ordered as bone marrow > serum > cerebrospinal fluid in Ph+ ALL bone marrow. In contrast, the concentration of dasatinib and imatinib was ordered as serum > bone marrow > cerebrospinal fluid. At the same time, flumatinib has a high probability to cross the blood-brain barrier, while the concentration of cerebrospinal fluid in the patients using Dasatinib was lower compared to the lower limit of detection in this study. Compared with Imatinib and Dasatinib, flumatinib exerted the most potent inhibitory effect on Ph+ ALL cell lines according to pharmacodynamic analysis of SUP-B15 cells.Conclusion: Flumatinib combined with chemotherapy could achieve good efficacy and safety in treating Ph+ ALL, with flumatinib in a high probability of crossing the blood-brain barrier. Flumatinib could be a superior choice to Dasatinib and Imatinib in cell experiments.